Seven Junior High School Science Curricular Programs: A Critique. - Zorn, Dr. Frederick J. (Science Education)
The article focuses on the seven science curricular programs for junior high school in the U.S. The programs represent a major improvement over traditional junior high school science teaching. Teachers are removed from the sole responsibility of curriculum building, determining what science concepts and processes to include, devising suitable experience for their development and providing needed materials and equipment. Students are actively involved in using science materials and equipment and have many first-handed experiences of a discovery, problem-solving nature. Coordinated, up-to-date resource materials provide appropriate sources of information.